2019
DOI: 10.1002/bse.2303
|View full text |Cite
|
Sign up to set email alerts
|

Exploring environmental, social, and governance disclosure effects on the S&P 500 financial performance

Abstract: Much of the literature measuring the relationship between environmental, social, and governance (ESG) scores and firm performance treats the score as a measure of sustainability performance. In this study, we treat a firm's ESG score as a demonstration of strategic choice in the level of transparency that results in increased firm performance as measured by Tobin's Q and return on assets. Performance differences are a result of choice moderated by the size of the firm as measured by employees and sales. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 41 publications
1
75
0
2
Order By: Relevance
“…In addition, to avoid biased results, we included several control variables, selected according to the previous literature (i.e., Amini, Bienstock, & Narcum, ; Amorelli & García‐Sánchez, ; Chen et al, ; Ghisetti, Marzucchi, & Montresor, ; Lee et al, ; Minutolo, Kristjanpoller, & Stakeley, ; Terrón Ibáñez, Gómez‐Miranda, Rodríguez, & Rodríguez Ariza, ; Tomas Siueia & Wang, ; Tsai & Liao, ; Tsai & Wang, ): “Size” is a numerical variable that represents the size of the company through the logarithm of total assets; “Leverage” is a numerical variable that represents financial leverage through the proportion of foreign funds and equity; “WC” is a numerical variable that represents the fund maneuver or liquidity of the company; “Dividend” is a numerical variable that represents the dividends accrued per share; “ForeignSales” is a numerical variable that represents the percentage of sales in markets other than domestic; “CapitalExp” is a numerical variable that represents the investment in physical capital relativized by sales; “R&D” is a numerical variable that represents the investment in R + D + i relativized by sales; “FirmAge” is a numerical variable that represents the age of the company; “CorpGovScore” is a numerical variable that represents the good corporate governance of the company through a score; and “SocialScore” is a numerical variable that represents the sustainability of social practices through a score. On the other hand, when we return the variable “Tobin Q ,” we control for economic profitability, “ROA.” Moreover, we control for “Country,” “Industry,” “Year,” “NCSRPI,” and the level of orientation towards the stakeholders of the company's country of origin (Amor‐Esteban, Galindo‐Vicente, & García‐Sánchez, ; Amor‐Esteban, Galindo‐Vicente, & García‐Sánchez, ; Amor‐Esteban, Galindo‐Villardón, & García‐Sánchez, ; Amor‐Esteban, García‐Sánchez, & Galindo‐Vicente, ; Amor‐Esteban, García‐Sánchez, & Galindo‐Vicente, ; García‐Sánchez, Cuadrado‐Ballesteros, & Frías‐Aceituno, ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to avoid biased results, we included several control variables, selected according to the previous literature (i.e., Amini, Bienstock, & Narcum, ; Amorelli & García‐Sánchez, ; Chen et al, ; Ghisetti, Marzucchi, & Montresor, ; Lee et al, ; Minutolo, Kristjanpoller, & Stakeley, ; Terrón Ibáñez, Gómez‐Miranda, Rodríguez, & Rodríguez Ariza, ; Tomas Siueia & Wang, ; Tsai & Liao, ; Tsai & Wang, ): “Size” is a numerical variable that represents the size of the company through the logarithm of total assets; “Leverage” is a numerical variable that represents financial leverage through the proportion of foreign funds and equity; “WC” is a numerical variable that represents the fund maneuver or liquidity of the company; “Dividend” is a numerical variable that represents the dividends accrued per share; “ForeignSales” is a numerical variable that represents the percentage of sales in markets other than domestic; “CapitalExp” is a numerical variable that represents the investment in physical capital relativized by sales; “R&D” is a numerical variable that represents the investment in R + D + i relativized by sales; “FirmAge” is a numerical variable that represents the age of the company; “CorpGovScore” is a numerical variable that represents the good corporate governance of the company through a score; and “SocialScore” is a numerical variable that represents the sustainability of social practices through a score. On the other hand, when we return the variable “Tobin Q ,” we control for economic profitability, “ROA.” Moreover, we control for “Country,” “Industry,” “Year,” “NCSRPI,” and the level of orientation towards the stakeholders of the company's country of origin (Amor‐Esteban, Galindo‐Vicente, & García‐Sánchez, ; Amor‐Esteban, Galindo‐Vicente, & García‐Sánchez, ; Amor‐Esteban, Galindo‐Villardón, & García‐Sánchez, ; Amor‐Esteban, García‐Sánchez, & Galindo‐Vicente, ; Amor‐Esteban, García‐Sánchez, & Galindo‐Vicente, ; García‐Sánchez, Cuadrado‐Ballesteros, & Frías‐Aceituno, ).…”
Section: Methodsmentioning
confidence: 99%
“…Economic performance is measured by ROAs, which is defined as the ratio of net profit to total assets. ROA reflects the efficiency of a firm's use of its assets to generate profits (Minutolo, Kristjanpoller, & Stakeley, 2019). Environmental performance is proxied by the RCO 2 , defined as tons of carbon dioxide emitted by the firm divided by total revenue.…”
Section: Empirical Analysismentioning
confidence: 99%
“…More specifically, Fanasch (2019) observed that individual reputation and ecocertification have a positive and significant impact on corporate performance. Additionally, the proponents of the instrumental stakeholder theory (Davis, 1973;Donaldson & Preston, 1995;Jones, 1995;Orlitzky et al, 2003) the Tobin Q (e.g., Konar & Cohen, 2001;Li, Liao, & Albitar, 2020;Minutolo, Kristjanpoller, & Stakeley, 2019;Wang et al, 2014) to the natural resource-based view of the firm (Hart, 1995), greener firms would be better able to differentiate their products than their less green peers. According to Manrique and Martí-Ballester, whereas civil society exerts strong pressures for environmental issues in developed countries (Cui, Liang, & Lu, 2015), the situation in developing countries is characterized by a less intense environmental awareness (Dagher & Itani, 2014…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%